Aerodynamic optimization design of aspirated highly loaded fan stage. (July 2019) - Zhang, Jinhuan; Zhou, Zhenggui; Cui, Cui
In this paper, an aerodynamic design method for an aspirated compressor/fan is developed. In the S2 through-flow design, the loss feedback is used to solve the inapplicability of the conventional loss model. In S1 profile design, an optimization design method is constructed in which the profile and the suction flow parameters are simultaneously handled as design parameters to couple the optimization design. A 3D optimization method is used to modify the profiles at the hub and tip of the rotor blade and the sweep and lean of the stator blade. An aspirated highly loaded fan stage (load coefficient of 0.69) was designed using the design method. A flow field simulation shows that at the design point, with a modest suction flow (4.84% of the inlet mass flow), very high isentropic efficiency (0.9213) is achieved, and the total pressure ratio (3.445) achieves its design goal (3.40), but the mass flow rate of the designed fan stage is 6.2% lower than the design goal. From the comparisons between the 2D flow fields on the S1 stream surfaces and the 3D flow fields at the corresponding blade spans, it is concluded that the flow presents nearly a form of a 2D S1 stream surface at most of the spans, and the 2D design method which is based on the S1/S2 stream surface in this paper is effective. Moreover, the flow is analyzed around the rotor root of the aspirated rotor, revealing a weak flow capacity in that area. This result suggests that desirable flow might not be set up when the designed profile has a large camber at the rotor blade root because the total pressure ratio cannot be improved without compromising the static pressure ratio.